Temperature-programmed reduction method for stabilization of the inorganic framework of SAPO-37 materials: promising catalysts for MTBE production - Shabana, K. Khadheejath; Narendranath, Soumya B.; Nimisha, N. P.; Venkatesha, N. J.; Sheetal, G.; Sakthivel, A. (Chemical Communications, 2024)
A temperature-programmed reduction method was developed to stabilize SAPO-37 and molybdenum-(oxy)-carbide-loaded SAPO-37 (SAP-37MoCR). The inorganic framework (Faujasite type SAPO-37) was retained for the first time even after treatment at 550 degrees C and was confirmed through powder XRD and SEM analysis. SAP-37MoCR exhibits strong acidic sites and is a promising catalyst for MTBE synthesis. Furthermore, the catalyst is stable and recyclable. Temperature-programmed reduction (TPR) is a new method of stabilising inorganic framework materials, viz., SAPO-37-type zeolite. The template could be converted into intermediate carbide species with metal ions.